Alone and under pressure: the transdiagnostic role of loneliness, stress, and psychological inflexibility in university students - Vaca-Gallegos, Silvia L.; Peñaherrera-Aguirre, Mateo; Batallas, Daniela; Paladines-Costa, Belén M.; López-Nuñez, Carla; Ruisoto, Pablo (Frontiers in Public Health, 2025)
IntroductionUniversity students face growingmental health challenges that demand both clinical and population-level strategies. Psychological inflexibility, perceived stress, and loneliness have been proposed as key transdiagnostic factors influencing mental health, yet their interrelationships remain unclear.MethodsWe conducted a cross-sectional survey among 7,905 students from 11 Ecuadorian universities. Validated instruments were used to assess psychological inflexibility (AAQ-II), perceived stress (PSS), loneliness (UCLA-3), anxiety and depression (PHQ-4), and life satisfaction (LSQ). Data were analysed using Sequential Canonical Analysis to examine direct and indirect associations among predictors and outcomes.ResultsAnalysis revealed a structured cascade: psychological inflexibility predicted perceived stress, which in turn predicted loneliness. All three variables contributed independently to mental health outcomes. Loneliness was the strongest predictor of anxiety, depression, and reduced life satisfaction, supporting its role as a chronic social stressor. Together, these factors explained 45% of the variance in a higher-order mental health factor and 35% of the variance in life satisfaction.DiscussionFindings underscore the need for integrated strategies in higher education that address both individual vulnerability and social isolation. Framed within Rose’s distinction between the causes of individual cases and the causes of population incidence, results highlight loneliness as a central target for preventive and clinical interventions.